1987
DOI: 10.1295/polymj.19.1173
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Limiting Viscosity Number and Radius of Gyration for Cellulose Dissolved in Aqueous 8% Sodium Hydroxide Solution

Abstract: ABSTRACT:A regenerated cellulose with a weight-average molecular weight Mw of 8.0 x l Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…It can be seen that the fluctuations increases slowly up until 40 C, after which the data become highly noisy. This suggests that strong attractive forces are acting upon the cellulose, something which does not agree with the result of Kamide et al (1987). These strong attractive forces cause the cellulose to aggregate into fewer, larger clusters with increasing temperature, which is the reason for the larger variance in the data at higher temperatures.…”
Section: Temperature Dependencementioning
confidence: 82%
“…It can be seen that the fluctuations increases slowly up until 40 C, after which the data become highly noisy. This suggests that strong attractive forces are acting upon the cellulose, something which does not agree with the result of Kamide et al (1987). These strong attractive forces cause the cellulose to aggregate into fewer, larger clusters with increasing temperature, which is the reason for the larger variance in the data at higher temperatures.…”
Section: Temperature Dependencementioning
confidence: 82%
“…NaOH ; (2) steam explosion process effectively breaks these hydrogen bonds (Okajima et al, 1990); (3) cellulose dissolves in aq. NaOH (Kamide et al, 1987); (4) regenerated cellulose films from aq. NaOH have high crystallinity, highly developed intramolecular hydrogen bonds, and selective uniplanar orientation of (11 -0) planes of cellulose Ⅱ crystal, and these structural parameters can be easily controlled by changing coagulation conditions such as coagulant concentration and temperature (Yang et al, 2007);…”
Section: Introductionmentioning
confidence: 99%
“…NaOH solution by a steam explosion method (Okajima and Kamide, 1984). Further study confirmed dissolution of cellulose in a dilute NaOH solution by a light scattering method (Kamide et al, 1987). The degree of the intramolecular hydrogen to the oral sensations of the product are pleasant.…”
Section: Introductionmentioning
confidence: 70%